Age and anthropometric indicators of highly qualified football players - Vladimir Perevoznik; Andrii Pertsukhov (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to determine the age and overall dimensions of the body of football players - participants of the World Cup 2018. Material & Methods: analysis, study and synthesis of domestic and foreign scientific and methodological literature allowed us to consider the model indicators of the sports capabilities of football players. Age and anthropometric indicators of highly qualified football players were considered. At the second stage, the studies were devoted to the study of indicators of the overall body dimensions of football players of the national teams of the participating teams of the 2018 World Cup. The study involved 736 football players aged 19 to 45 years. Such research methods as the analysis of scientific and methodical literature and methods of mathematical statistics were used. Results: presents the age and anthropometric indicators of football players - participants of the 2018 World Cup. It has been established that football players participating in the 2018 World Cup have characteristic overall body dimensions and a number of their differences depending on the sporting role. Football players do not unite in one group, but are divided into classes according to the game specialization, which completely negates the thesis about the "universal" football player. Conclusions: the data obtained suggest that the peak of sportsmanship in football is in the age range from 25 to 29 years. This age range included 342 people from 736 participants of the 2018 World Cup.